2017
DOI: 10.1136/bmjopen-2017-016189
|View full text |Cite
|
Sign up to set email alerts
|

Association between mothers’ screening uptake and daughters’ HPV vaccination: a quasi-experimental study on the effect of an active invitation campaign

Abstract: ObjectivesIn Emilia-Romagna, the Human Papillomavirus (HPV) vaccination campaign started in 2008 offering free vaccines for 1996 and 1997 cohorts. Systematic active invitation was implemented for the 1997 cohort. Our study aimed at measuring the impact of the active invitation campaign on HPV vaccine coverage and on coverage inequalities in 11-year-old girls. Second, we evaluated the effect of the HPV vaccination campaign on participation in cervical cancer screening by mothers of target girls.MethodsWe collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
0
12
0
1
Order By: Relevance
“…In 2015, the transition to human papillomavirus (HPV)‐based screening of women aged 30–64 years was initiated in accordance with national guidelines . Previously, in 2008, a regional HPV vaccination campaign had been implemented starting from girls in the 1996 and 1997 birth cohorts . These have currently not yet entered the target population of the screening programme, which allows to exclude any bias in the results of this study.…”
Section: Methodsmentioning
confidence: 99%
“…In 2015, the transition to human papillomavirus (HPV)‐based screening of women aged 30–64 years was initiated in accordance with national guidelines . Previously, in 2008, a regional HPV vaccination campaign had been implemented starting from girls in the 1996 and 1997 birth cohorts . These have currently not yet entered the target population of the screening programme, which allows to exclude any bias in the results of this study.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, a study from Italy indicated lower vaccination coverage rates against the HPV in foreigners, compared to Italian citizens [35]. Furthermore, other studies involving female adolescents of national minorities from degraded areas, found that the rates of HPV vaccination were lower compared to those of privileged ones [36,37].…”
Section: Nationalitymentioning
confidence: 90%
“…A pesquisa produzida na Itália por Venturelli et al (2017), preocupou-se em medir o impacto de campanhas de incentivo à vacinação contra o HPV e a percepção das desigualdades entre meninas de 11 anos. Além disso, objetivou-se avaliar o efeito dessas campanhas educativas na participação no rastreamento de casos de câncer cervical por mães de meninas-alvo.…”
Section: Fonte: Autoresunclassified